High quality video in high dynamic range scenes from interlaced dual-ISO footage - Rodríguez, Raquel Gil; Bertalmío, Marcelo (Electronic Imaging, 2016)
In this paper we present a simple and affordable method to generate high quality video from a high dynamic range scene. It is performed without utilizing extra lighting, neither alternating exposures, nor operating with dual-camera set-ups. Our input is an interlaced video alternating row pairs with different ISO values, as some DSLR camera models can provide. The proposed algorithm involves two main steps: first the computation of two single-ISO full-frame images (one for each ISO value) using an inpainting-based deinterlacing method, followed by their combination into a single frame by a weighted average. This results in a high dynamic range frame, containing all the details in bright and dark areas at the same time, that is finally tone-mapped into a low dynamic range frame for display purposes. Current results show this is a practical and cost-effective method that produces outputs free of ghosting artifacts and with very little noise.